Speaking for Academic Purposes Course: An Analysis of Language Functions - Menggo, Sebastianus; Suastra, I Made; Budiarsa, Made; Padmadewi, Ni Nyoman (e-Journal of Linguistics; Vol 13 No 2 (2019): e-jl-JulyDO - 10.24843/e-JL.2019.v13.i02.p10, 2019)
Speaking as the most demanding skill to be mastered in the ESL/EFL teaching context. This is caused by the prime priority of students who want to study English in order to be able to use English for communicative purposes. Knowledge of language functions has a vital role in supporting a speaker to be more involved in the real interaction. The aim of this study is to analyze the use of language functions in the speaking for academic purposes course. This study conducted at the English department students which altogether 33 persons in STKIP Santu Paulus Ruteng, Indonesia. Then data were collected through observation, field note  and natural recorded when the respondents were doing the English speaking exercises at the speaking for academic purposes course. Data collection were done during eight meetings and only language functions utterances of those respondents were analyzed. The utterances recorded are expected to be representative of the whole the language functions. Utterances produced  by respondents were recorded precisely by the researchers. The result showed that there are five types of language functions found, namely interactive function, informative function, manipulative function, motivative function and directive functions. Those functions are reciprocal. Speaking practitioners are suggested to provide the knowledge of language functions in the speaking learning process.